EL GENERO ALBERTELLA (TRILOBITE) EN EL CAMBRICO MEDIO DE SAN JUAN (ARGENTINA) (Ameghiniana, 2013)
Two new species of trilobite genus Albertella of the Lower Middle Cambrian of Argentina "Albertella zone" are described. The fossils was collected in the limestones sequence of the La Laja Formation in the Geological Province of the Precordillera (San Juan, Argentina). Correlation with the North Hemisphere Cambrian fauna was established.